Running and posture - D'Isanto, T.; Pisapia, F.; D'Elia, F. (Journal of Human Sport & Exercise, 2019)
An athlete, to get the best result, brings the body to its maximum through targeted and personalized training. To do this, the athlete must be in a state of psycho-physical balance and it is possible not only thanks to proper training, but above all to a correct posture. It depends on many factors and once analysed, there are different ways to improve it. The aim of the research is to demonstrate, from the recognition of scientific literature, how posture can influence sporting performance, in particular in a fast-running race, of an élite athlete and how it can be improved. Therefore, the method adopted is that of the "Prisma" protocol, with the comparison of reviews of carefully selected scientific products. The data reported in the research describe a series of mechanisms according to which our body carries out a series of adaptations, which over time, can be fixed as postural defects and which can negatively influence performance. It is therefore necessary for the athlete to acquire a good running technique by performing a series of exercises aimed at improving the tone of the various muscle areas, joint mobility, coordination and harmonious movements, associated with a targeted postural and corrective exercise program, instead, to recover the flawed attitudes. In conclusion, it is possible to affirm how, through postural correction, and therefore of specific exercises of postural re-education and muscle tone, it is possible to achieve balance, well-being and an improvement in athletic performance.